The Asuka-90 meteorites collection from Antarctica: Searching, initial processing and preliminary identification - Yanai, Keizo; Shiraishi, Kazuyuki; Kojima, Hideyasu (National Institute of Polar Research, 1994)
P(論文) Over 2400 meteorites have been collected by the Japanese Antarctic Research Expeditions (JARE) on the bare icefield around the Sor Rondane Mountains in Queen Maud Land, East Antarctica, since 1986. The Asuka wintering party of JARE-30 (1989-91) carried out a meteorite search during a geological survey, and collected 48 meteorites on the bare icefield around Mt. Balchen in the eastern part of the mountains on November 1990. During the initial processing, the specimens were officially named the Asuka (A)-9001 to A-9048,in order of discovery. The Asuka-90 meteorites collection was cataloged by the National Institute of Polar Research (NIPR) with details of find, weight, dimensions, brief identification and classification data, and comments. According to the preliminary identification, the Asuka-90 meteorites include one achondrite and 47 ordinary chondrites, the total weight being 11.48kg. The largest specimen is an L chondrite of about 3.27kg. The Asuka-90 meteorites included no irons, no stony-irons and no carbonacous chondrites. departmental bulletin paper